A Critical Discourse Analysis on Implicit Opinion of Russian Dissatisfaction upon Putin Regime as Expressed in Article âThe Civil Archipelago : How Far Can The Resistance To Vladimir Putin Go?â - Marlangen, Niken Wresthi Kinanthi; Tallapessy, Albert; Diana, Sabta (Publika Budaya, 2014)
This research discusses the implicit opinion about Russian people dissatisfaction upon Putin regime as expressed in article The Civil Archipelago: How Far Can the Resistance to Vladimir Putin Go? This article was published by an American popular mass media, The New Yorker. The main goal of this research is to uncover the hidden opinion that it is unable to emerge an ambiguous interpretation. The implicitness is analysed by using Pottsâs (2005) theory of Conventional Implicature. The domains used are Nominal Appositive and Supplementary Relative. In order to see the relationship between the implication and the ideological effect of mass media, a critical discourse analysis is applied as well. Namely by taking the socio-political relationship of Russia and US into account. Keywords: critical discourse analysis, conventional implicature, supplementary relative, nominal appositive, US-Russiaâs socio-political relationship